Better Than the Real Thing: Processed Reality in Victorian Art and Fiction - Béatrice Laurent (Cahiers Victoriens et Edouardiens)
This paper investigates the paradoxical and composite nature of realist photography and fiction. In the 1850s, strategies of aggregation were part of the regular compositional practice of Victorian painters, from the Pre-Raphaelite William Holman Hunt to William Powell Frith. The artistic re-composition of reality was taken on board by early photographers such as Henry Peach Robinson. Various forms of aggregation, including juxtaposition and superimposition were used to create images that looked ‘real’. Thus, filtered and fictionalised reality came to replace the ocular experience in the interaction between the individual subject and the outside world, to the extent that novelists were impacted by this procedure. The article navigates from the visual arts to fiction and vice-versa to show that the same artistic strategies were at work in both worlds, and how fiction influenced visual artists and conversely how the visual arts were a source of inspiration for Victorian novelists. The argument includes considerations on the impact of scientific instruments as well, particularly optical instruments. The result is that one can see how complex and contrived realism was in its effort to produce verisimilitude.